2016
DOI: 10.1021/acs.jafc.6b01725
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Native Flavanols during Fermentation and Roasting Does Not Necessarily Reduce Digestive Enzyme-Inhibiting Bioactivities of Cocoa

Abstract: Polyphenol profiles and in vitro digestive enzyme inhibitory activities were compared between cocoa extracts from unfermented beans (UB), fermented beans (FB), unfermented liquor (UL), and fermented liquor (FL). Total polyphenols, total flavanols, and individual flavanols were significantly different between UB/FB and UL/FL. All extracts effectively inhibited α-glucosidase (lowest IC50 = 90.0 μg/mL, UL) and moderately inhibited α-amylase (lowest IC50 = 183 μg/mL, FL) and lipase (lowest IC25 = 65.5 μg/mL, FB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Our reported data suggest that distinct activities of cocoa powder are not consistently reduced by phenol losses as a result of alkalization process. A similar observation was reported by Ryan and others (), who demonstrated that the loss of native flavanols during cocoa roasting and fermentation is not necessarily connected with the reduction in the digestive enzymes inhibition. A potential explanation for these observations is the formation of new bioactive compounds during alkalization that have prominent antimicrobial but not antioxidant activity.…”
Section: Resultssupporting
confidence: 88%
“…Our reported data suggest that distinct activities of cocoa powder are not consistently reduced by phenol losses as a result of alkalization process. A similar observation was reported by Ryan and others (), who demonstrated that the loss of native flavanols during cocoa roasting and fermentation is not necessarily connected with the reduction in the digestive enzymes inhibition. A potential explanation for these observations is the formation of new bioactive compounds during alkalization that have prominent antimicrobial but not antioxidant activity.…”
Section: Resultssupporting
confidence: 88%
“…Polyphenol-rich extracts were made from raw beans, the fermented cocoa beans, and powders for all seven treatments, as described previously [13,30]. The Folin-Ciocalteu colorimetric assay was used to approximate the total phenolic content of the freeze-dried cocoa extracts, and total flavanols were measured by the 4-dimethylaminocinnamaldehyde (DMAC) colorimetric assay, as previously described in Dorenkott et al [12].…”
Section: Polyphenol Extraction and Characterizationmentioning
confidence: 99%
“…as potential inhibitors [16]. While isolated PCs are effective α-glucosidase inhibitors, we recently found that various cocoas were effective inhibitors of α-glucosidase, despite large reductions in native flavanols as a result of fermentation and roasting [13]. These results challenge the idea that losses of native flavanols inherently reduces all bioactivity of cocoa and, therefore, warrant further investigation into the factors that determine α-glucosidase inhibition.…”
mentioning
confidence: 93%
See 2 more Smart Citations